Production Technology of Modified Expanded Clay Lightweight Concrete for Floating Structures - Sergii O. Kroviakov; Eng. Andrey V. Mishutin (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
Concrete ships (floating docks, hotels, houses, marinas, oil platforms) are being built in many countries around the world. For such ships previously used mainly heavy concrete. Recently, for concrete floating structures often use lightweight aggregate concrete. Using expanded clay lightweight concretes reduces the weight of the construction. At reducing the weight load lifting of the floating structure is increased. The use of lightweight concrete improves people’s occupation and equipment on a reinforced concrete ship. Influence of composition expanded clay concrete on its properties has been found. At the first stage, were investigated lightweight concrete based on the processed by hydrophobisator gravel. In the second phase were investigated concretes with silica fume. Planned three-factor experiment was conducted. Such concrete composition were varied: the amount of cement (500-600 kg/m3), silica fume (0-50 kg/m3) and superplasticizer S-3 (0.5-1%). Concretes were made from equal mixtures mobility P2 (4-6 cm). It is found that the compressive strength of concrete is in the range of 32 to 43 MPa. By increasing the amount of cement strength increases, but this increase is not linear type. Tensile strength of concrete was in the range of 5.6 to 7.0 MPa. Water-resistant concrete was in the range of W4 to W12. When administered to 30-35 kg/m3 silica fume of about 2 MPa increases compressive strength expanded clay lightweight concrete and 0.3 MPa the tensile strength increases with bending. By increasing the amount of additive S-3 is significantly increased compressive strength concrete. However, the introduction of additives increases tensile strength is less when bending. Due to the introduction of the optimal amount of silica fume and S-3 water resistance of concrete is increased by about 40-50%. Thus, the modified expanded clay lightweight concrete has a relatively low bulk density with high strength. They can be used in thin-walled construction of hydraulic structures, in particular floating docks, houses and hotels.